Substrate metabolism and exercise performance with caffeine and carbohydrate intake - Hulston, C. J.; Jeukendrup, A. E. (Medicine & Science in Sports & Exercise, 2008)
Purpose: 1) To investigate the effect of caffeine on exogenous carbohydrate (CHO) oxidation and glucose kinetics during exercise; and 2) to determine whether combined ingestion of caffeine and CHO enhanced cycling performance compared with CHO alone.